2016
DOI: 10.1158/2159-8290.cd-15-0224
|View full text |Cite
|
Sign up to set email alerts
|

Targeting YAP-Dependent MDSC Infiltration Impairs Tumor Progression

Abstract: The signaling mechanisms between prostate cancer cells and infiltrating immune cells may illuminate novel therapeutic approaches. Here, utilizing a prostate adenocarcinoma model driven by loss of Pten and Smad4, we identify polymorphonuclear myeloid-derived suppressor cells (MDSCs) as the major infiltrating immune cell type and depletion of MDSCs blocks progression. Employing a novel dual reporter prostate cancer model, epithelial and stromal transcriptomic profiling identified Cxcl5 as a cancer-secreted chemo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
430
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 439 publications
(448 citation statements)
references
References 41 publications
15
430
1
2
Order By: Relevance
“…Numerous reports describe the presence of MDSC in murine tumors (reviewed in [22, 23]) and recent studies demonstrated that tumor associated MDSC have an important role in tumor progression [24, 25]. In humans, recent studies described the presence of MDSC in glioblastoma [26], urothelial carcinoma [27], pancreatic adenocarcinoma [7], and breast cancer [28].…”
Section: Regulation Of Mdsc Recruitment To Tumorsmentioning
confidence: 99%
“…Numerous reports describe the presence of MDSC in murine tumors (reviewed in [22, 23]) and recent studies demonstrated that tumor associated MDSC have an important role in tumor progression [24, 25]. In humans, recent studies described the presence of MDSC in glioblastoma [26], urothelial carcinoma [27], pancreatic adenocarcinoma [7], and breast cancer [28].…”
Section: Regulation Of Mdsc Recruitment To Tumorsmentioning
confidence: 99%
“…YAP has also been identified in human MPM and is correlated with tumorigenesis and cancer development, suggesting YAP is a therapeutic target for treating advanced unresectable MPM 19, 20, 21. YAP regulates tumour‐associated immune cells such as myeloid‐derived suppressor cells (MDSCs) and tumour‐associated macrophages (TAMs) 22, 23. YAP may be involved in the immune checkpoint 22, 23.…”
Section: Introductionmentioning
confidence: 99%
“…Almost all of the roles of YAP-1 have been identified from tumor cells; a little knowledge has been identified concerning its roles in the immune cell. However, several studies have revealed its role in immunosuppression [19,20], it is meaningful to investigate its role in Treg development in HCC.…”
Section: Introductionmentioning
confidence: 99%